Kemacetan Jaringan Akibat Media Sosial: Menganalisis Dampaknya terhadap Efisiensi Transmisi Data Nirkabel - Kuncoro, Wreda Agung; Santoso, Lukman (Jurnal Ilmiah Sistem Informasi, 2025)
The increasing use of social media has significantly impacted wireless network performance, particularly in data transmission efficiency. This study aims to analyze the impact of social media usage on network congestion and wireless data transmission efficiency. Experimental and quantitative methods were employed, utilizing direct network traffic measurement and simulation techniques. The study assessed key parameters, including throughput, latency, packet loss, and jitter, to evaluate network congestion levels caused by social media activities such as video streaming, image uploads, and real-time communication. The results indicate a 15–30% decrease in throughput, an increase in latency from 30 ms to 120 ms, a packet loss surge from 0.5% to 4–7%, and a jitter increase from 10 ms to 50 ms during peak hours of social media usage. The study also found that channel bonding techniques can improve throughput by up to 63.6% under controlled interference conditions. These findings highlight the necessity of effective traffic management strategies, including 5G network deployment, machine learning-based traffic optimization, and Quality of Service (QoS) implementation, to mitigate network congestion issues caused by the exponential growth of social media users.